A novel autosomal dominant GREB1L variant associated with non-syndromic hearing impairment in Ghana - Samuel Mawuli Adadey; Elvis Twumasi Aboagye; Kevin Esoh; Anushree Acharya; Thashi Bharadwaj; Nicole S. Lin; Lucas Amenga-Etego; Gordon A. Awandare; Isabelle Schrauwen; Suzanne M. Leal; Ambroise Wonkam (BMC, 2022)
Abstract Background Childhood hearing impairment (HI) is genetically heterogeneous with many implicated genes, however, only a few of these genes are reported in African populations. Methods This study used exome and Sanger sequencing to resolve the possible genetic cause of non-syndromic HI in a Ghanaian family. Results We identified a novel variant c.3041G > A: p.(Gly1014Glu) in GREB1L (DFNA80) in the index case. The GREB1L: p.(Gly1014Glu) variant had a CADD score of 26.5 and was absent from human genomic databases such as TopMed and gnomAD. In silico homology protein modeling approaches displayed major structural differences between the wildtype and mutant proteins. Additionally, the variant was predicted to probably affect the secondary protein structure that may impact its function. Publicly available expression data shows a higher expression of Greb1L in the inner ear of mice during development and a reduced expression in adulthood, underscoring its importance in the development of the inner ear structures. Conclusion This report on an African individual supports the association of GREB1L variant with non-syndromic HI and extended the evidence of the implication of GREB1L variants in HI in diverse populations.